The Plasmodium falciparum Nuclear Protein Phosphatase NIF4 Is Required for Efficient Merozoite Invasion and Regulates Artemisinin Sensitivity - Xiaotong Zhu; Siqi Li; Chengqi Wang; Yuanchao Yu; Jingjing Wang; Lu He; Faiza Amber Siddiqui; Lumeng Chen; Liying Zhu; Dan Zhou; Junling Qin; Jun Miao; et al. (mBio, 2022)
ABSTRACT Artemisinin resistance in Plasmodium falciparum has been associated with a mutation in the NLI-interacting factor-like phosphatase PfNIF4, in addition to the mutations in the Kelch13 protein as the major determinant. We found that PfNIF4 was predominantly expressed at the schizont stage and localized in the nuclei of the parasite. To elucidate the functions of PfNIF4 in P. falciparum, we performed PfNIF4 knockdown (KD) using the inducible ribozyme system. PfNIF4 KD attenuated merozoite invasion and affected gametocytogenesis. PfNIF4 KD parasites also showed significantly increased in vitro susceptibility to artemisinins. Transcriptomic and proteomic analysis revealed that PfNIF4 KD led to the downregulation of gene categories involved in invasion and artemisinin resistance (e.g., mitochondrial function, membrane, and Kelch13 interactome) at the trophozoite and/or schizont stage. Consistent with PfNIF4 being a protein phosphatase, PfNIF4 KD resulted in an overall upregulation of the phosphoproteome of infected erythrocytes. Quantitative phosphoproteomic profiling identified a set of PfNIF4-regulated phosphoproteins with functional similarity to FCP1 substrates, particularly proteins involved in chromatin organization and transcriptional regulation. Specifically, we observed increased phosphorylation of Ser2/5 of the tandem repeats in the C-terminal domain (CTD) of RNA polymerase II (RNAPII) upon PfNIF4 KD. Furthermore, using the TurboID-based proteomic approach, we identified that PfNIF4 interacted with the RNAPII components, AP2-domain transcription factors, and chromatin-modifiers and binders. These findings suggest that PfNIF4 may act as the RNAPII CTD phosphatase, regulating the expression of general and parasite-specific cellular pathways during the blood-stage development. IMPORTANCE Protein phosphorylation regulates a multitude of cellular processes. The eukaryotic FCP1 phosphatase acts as a CTD-phosphatase to critically balance the phosphorylation status of the CTD of the RNAPII, controlling the accurate execution of the transcription process. Here, we identified PfNIF4 as the FCP1-like phosphatase in P. falciparum. PfNIF4 KD specifically downregulated genes involved in merozoite invasion, resulting in the attenuation of this process. Consistent with the earlier finding of the association of PfNIF4 mutations with artemisinin resistance in Southeast Asian parasite populations, PfNIF4 KD significantly increased in vitro susceptibility to artemisinins. The regulation of these cellular processes in P. falciparum by PfNIF4 is likely realized through RNAPII-mediated transcription, because PfNIF4 was found to interact with RNAPII subunits and KD of PfNIF4 caused CTD hyperphosphorylation. Our results reveal the functions of the PfNIF4 phosphatase in controlling the transcription of invasion- and resistance-related genes in the malaria parasite.